Market Access and Welfare under Free Trade Agreements : Textiles under NAFTA - Cadot, Olivier; Carrere, Celine; de Melo, Jaime; Portugal-Perez, Alberto (Published by Oxford University Press on behalf of the World Bank, 2014)
The effective market access granted to textiles and apparel under the North American Free Trade Agreement (NAFTA) is estimated, taking into account the presence of rules of origin. First, estimates are provided of the effect of tariff preferences combined with rules of origin on the border prices of Mexican final goods exported to the United States (U.S.) and of U.S. intermediate goods exported to Mexico, based on eight-digit harmonized system tariff-line data. A third of the estimated rise in the border price of Mexican apparel products is found to compensate for the cost of complying with NAFTA's rules of origin, and NAFTA is found to have raised the price of U.S. intermediate goods exported to Mexico by around 12 percent, with downstream rules of origin accounting for a third of that increase. Second, simulations are used to estimate welfare gains for Mexican exporters from preferential market access under NAFTA. The presence of rules of origin is found to approximately halve these gains.